Perancangan Katalog Digital untuk Representasi Stasiun Lokal Bandung Raya Melalui Fotografi Jalanan Monokromatik - Diaz Nafi; Maya Purnamasari; Saripudin Saripudin (Jurnal Ilmu Sosial dan Ilmu Politik)
Public transportation plays a crucial role in enhancing community mobility, significantly impacting economic and social aspects. In Bandung, there are 13 local stations in the Bandung Raya area, stretching from Padalarang to Cicalengka, including Padalarang, Gadobangkong, Cimahi, Cimindi, Ciroyom, Bandung, Cikudapateuh, Kiaracondong, Gedebage, Cimekar, Rancaekek, Haurpugur, and Cicalengka stations. This study aims to interpret the conditions across these stations through monochromatic photography. Street photography is selected as the approach due to its ability to capture the dynamic and ever-changing human activities. The research employs a descriptive qualitative method, gathering data from street photography literature, monochromatic works, and direct field observations. The result is a collection of 65 monochromatic photographs that depict various occurrences at each station. These works are compiled into a digital catalog accessible via the issuu.com website. This catalog not only serves as a visual documentation of the stations' dynamics but also aims to raise public awareness of the cultural and social significance of public transportation in the Bandung Raya area. Through this catalog, the conditions and dynamic life at the local stations of Bandung Raya are visually and comprehensively represented.